$\Huge{\text{CỨU MÌNH VỚI!!}}$ $P= (\frac{1}{1-√x} – \frac{1}{1+√x})(1-\frac{1}{√x})$ với $x>0; x\neq1$

Question

$\Huge{\text{CỨU MÌNH VỚI!!}}$
$P= (\frac{1}{1-√x} – \frac{1}{1+√x})(1-\frac{1}{√x})$ với $x>0; x\neq1$

in progress 0
Josie 2 tháng 2021-09-09T06:57:16+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-09-09T06:59:05+00:00

    Đáp án:

    `P=-2/(1+\sqrt{x})`

    Giải thích các bước giải:

     Với `x>0;x\ne 1`

    Ta có:

    `P=(1/(1-\sqrt{x})-1/(1+\sqrt{x}))(1-1/\sqrt{x})`

    `=((1+\sqrt{x})-(1-\sqrt{x}))/((1+\sqrt{x})(1-\sqrt{x})).(\sqrt{x}/\sqrt{x}-1/\sqrt{x})`

    `=(1+\sqrt{x}-1+\sqrt{x})/((1+\sqrt{x})(1-\sqrt{x})).(\sqrt{x}-1)/\sqrt{x}`

    `=(2\sqrt{x})/((1+\sqrt{x})(1-\sqrt{x})).(\sqrt{x}-1)/\sqrt{x}`

    `=(2\sqrt{x}.(\sqrt{x}-1))/((1+\sqrt{x})(1-\sqrt{x}).\sqrt{x})`

    `=(-2\sqrt{x}.(1-\sqrt{x}))/((1+\sqrt{x})(1-\sqrt{x}).\sqrt{x})`

    `=-2/(1+\sqrt{x})`

    Vậy với `x>0;x\ne 1` thì `P=-2/(1+\sqrt{x})`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )